(3gOjI Chdi GdHUGFQ hGdCHUGQ aj eYQag BNQ Gddjd hGdfgGQs - (3GdSLGYj , CMeO Hf CMeO Hf eMeO GdSLGYj GdHOQGhj GdGRgQj, TgGH GdOjf,J (B1197 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3abO CeQfi HYV GddBLdg GdCYjGf Cf CTQM dg efXheg GdTjN GdUGdM s
(3BNQgG (B:s
(3hEMSGf (B: (3YWa JaSjQ hGddg CYde GfJgi eG CaGOg GdeMbb GdeObb GdYdGeg GdTjN CMeO GdTLGYi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B104s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B93 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B154s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B324 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B109 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(181) s
Keywords: (3Gdadcs